A THERMOELECTRIC SEMICONDUCTOR DEVICE WITH A HIGH TEMPERATURE GRADIENT - S. M. Gadjiyevа; D. A. Chelushkin (Вестник Дагестанского государственного технического университета: Технические науки)
In the article the thermoelectric device, which heated junctions spatially distant from the cold junctions to reduce parasitic losses between the conductive junctions.